KESALAHAN PENAFSIRAN WACANA - Astuti, Sri Puji (Sabda: Jurnal Kajian Kebudayaan, 2016)
Misinterpretation of discourse often occurs in daily life. In conveying the idea or message actually speaker or writer has tried to convey the idea in order that hearer clear. However, in reality it is not. Why there was an error of interpretation of discourse in daily life are discussed in this paper. This study analyzes data in the form of oral discourse and written discourse in society that contains errors of interpretation. The method used to collect data is by recording technique and further noted the data that were analyzed by using discourse interpretation referring to the context. This study results that misinterpretation discourse was usually caused by the speaker who did not know the hearer, pause used by the speaker was not clear, speakers was wrong to write the word, hearer misheard, hearer did not know the word or term, hearer did not understand, hearer was not appropriate, topics of the conversation changed, the difference between the speaker's presuppositions and hearer, and time setting